دراسة جرثومية لالتهابات الأذن الوسطى - إبراهيم, مصطفى; يوسف, يوسف; محمد, حسن (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 100 مريض من مراجعي العيادة الأذنية في مشفى الأسد الجامعي في اللاذقية بين عامي 2002-2003 واللذين لديهم شكوى التهاب أذن وسطى. وكان منهم 22 مريضاً يشكون من التهاب أذن وسطى حاد قيحي، و6 مرضى يشكون من التهاب أذن وسطى حاد غير قيحي، و7 مرضى يشكون من التهاب غشاء طبل فقاعي، و21 مريضاً يشكون من التهاب أذن وسطى إفرازي، و44 مريضاً يشكون من التهاب أذن وسطى قيحي مزمن. وتوزعت أعمار المرضى على الفئات العمرية التالية: أقل من ثلاث سنوات 15 مريضاً بنسبة 15%. بين 3- 6 سنوات 32 مريضاً بنسبة 32%. بين 6-20 سنة 15 مريضاً بنسبة 15%. أكبر من 20 سنة 38 مريضاً بنسبة 38%. وكانت نسبة الذكور 57% ونسبة الإناث 43%. وكانت الشكاوى الرئيسية للمرضى كالآتي: سيلان قيحي من الأذن المصابة لدى 62 مريضاً بنسبة 62%. نقص في السمع في الأذن المصابة لدى 21 مريضاً بنسبة21%. الألم الأذني لدى 15 مريضاً بنسبة 15%. سيلان مصلي مدمى من الأذن المصابة لدى مريضين بنسبة 2% . وشكلت العنقوديات المذهبة نسبة 17 % من نتائج الزرع، والمقيحات الزرق نسبة10%، والمكورات الرئوية نسبة 10%، والمستدميات النزلية نسبة9%. وكانت أكثر الصادات تأثيراً هي الكلورام فينيكول والأموكسيسيلين مع حمض الكلافولينيك والسفترياكسون . The research included one hundred patients of the visitors of the E.N.T. clinic in Al-Assad University Hospital in Lattakia between 2002 -2003 who had the complaint of otitis media . From these patients there were 22 patients who had acute suppurative otitis media ,6 patients had acute non suppurative otitis media ,7 patients had bullous meryngitis, 21 patients had secretory otitis media ,and 44 patients had chronic suppurative otitis media. The age of the patients distributed in the following age groups : Younger than three years :15 patients forming 15%. Between 3-6 years :32 patients forming 32%. Between 6-20 years :15 patients forming 15%. Bigger than 20 years :38 patients forming 38%. The male ratio was 57% and the female ratio was 43%. The main complaints of the patients were as follows: Otorrhea from the afflicted ear in 62 patients forming 62%. Hearing loss in the afflicted ear in 21 patients forming 21%. Ottic pain in15 patients in the afflicted ear in 15 patients forming 15%. Hemoserous otorrhea from the afflicted ear in 2 patients forming 2%. The staphylococcus aureus formed 17% of the culture results ,the pseudomonas aeruginosa formed 10%,the streptococcus pneumoniae formed 10%,and the haemophilus influenzae formed 9% . The most effective antibiotics were chloram phenicol ,amoxycillin with clavolinic acid, and ceftriaxon .